Normal people : a novel - Rooney, Sally (Hogarth, 2019)
At school Connell and Marianne pretend not to know each other. He<U+2019>s popular and well-adjusted, star of the school football team, while she is lonely, proud, and intensely private. But when Connell comes to pick his mother up from her job at Marianne<U+2019>s house, a strange and indelible connection grows between the two teenagers<U+2014>one they are determined to conceal. A year later, they<U+2019>re both studying at Trinity College in Dublin. Marianne has found her feet in a new social world while Connell hangs at the sidelines, shy and uncertain. Throughout their years at university, Marianne and Connell circle one another, straying toward other people and possibilities but always magnetically, irresistibly drawn back together. And as she veers into self-destruction and he begins to search for meaning elsewhere, each must confront how far they are willing to go to save the other.